2023
DOI: 10.1159/000533550
|View full text |Cite
|
Sign up to set email alerts
|

An Asymptomatic Patient with Colonic Leiomyoma

Saad Alkhowaiter,
Abdulmalik Alsheikh,
Ammar Alotaibi

Abstract: Subepithelial lesions (SELs) originating from muscularis mucosae of the colon are very rare findings on endoscopy. Appropriate management of SELs involves making a correct diagnosis and estimating their malignant potential. In this case study, a 58-year-old Saudi man presented with a small, 8-mm sigmoid polyp during screening colonoscopy. The polyp was removed by hot snare polypectomy and sent to pathology laboratory. Report showed an unremarkable colonic mucosa and underlying well-circumscribed submucosal les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the colon, most lesions are adenomas (mostly tubulo/tubulo-villous with low-grade dysplasia). Nevertheless, benign proliferations of nonepithelial cells such as those from underlying smooth muscle layers, known as leiomyomas, can arise in the colon and are typically found incidentally [4]. Small sessile polyps have been reported as the most common presentation of colonic leiomyomas; however, there have also been reports of leiomyomas of the colon presenting as firm, well-circumscribed, intraluminal, semi-pedunculated, or pedunculated polyps [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the colon, most lesions are adenomas (mostly tubulo/tubulo-villous with low-grade dysplasia). Nevertheless, benign proliferations of nonepithelial cells such as those from underlying smooth muscle layers, known as leiomyomas, can arise in the colon and are typically found incidentally [4]. Small sessile polyps have been reported as the most common presentation of colonic leiomyomas; however, there have also been reports of leiomyomas of the colon presenting as firm, well-circumscribed, intraluminal, semi-pedunculated, or pedunculated polyps [6].…”
Section: Discussionmentioning
confidence: 99%
“…When the lesions present as submucosal, an endoscopic ultrasound could be useful in determining therapeutic strategies, providing valuable information on the size and extension of the tumor [3]. Moreover, flat lesions may require the use of endoscopic mucosal resection or endoscopic submucosal dissection techniques [4]. Xu et al studied 106 patients with gastrointestinal leiomyomas diagnosed through endoscopic ultrasonography (EUS) and concluded that EUS had a very important diagnostic value for gastrointestinal leiomyomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation